2003
DOI: 10.1002/pri.287
|View full text |Cite
|
Sign up to set email alerts
|

Living with chronic renal failure: patients' experiences of their physical and functional capacity

Abstract: The results of the study will contribute to our understanding of how these patients experience their daily lives, and will help when meeting patients with chronic renal failure. This knowledge enables physiotherapists to focus rehabilitation training on problem areas that are important to patients themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 15 publications
2
71
0
5
Order By: Relevance
“…Although fatigue has emerged as a dominant theme across several qualitative studies on the experience of living with ESKD (e.g., Hagren, Pettersen, Severinsson, Lützén, & Clyne, 2001; Heiwe, Clyne, & Dahlgren, 2003), at present only four fatigue‐specific qualitative studies are available among dialysis patients (Horigan & Barroso, 2016; Horigan, Schneider, Docherty, & Barroso, 2013; Lee, Lin, Chaboyer, Chiang, & Hung, 2007; Yngman‐Uhlin, Friedrichsen, Gustavsson, Fernström, & Edéll‐Gustafsson, 2010). These studies offer valuable insights into the dominance of biomedical causal attributions for fatigue, the role of sleep quality in further exacerbating fatigue, and pervasiveness of passive fatigue management strategies (Horigan et al ., 2013; Lee et al ., 2007; Yngman‐Uhlin et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although fatigue has emerged as a dominant theme across several qualitative studies on the experience of living with ESKD (e.g., Hagren, Pettersen, Severinsson, Lützén, & Clyne, 2001; Heiwe, Clyne, & Dahlgren, 2003), at present only four fatigue‐specific qualitative studies are available among dialysis patients (Horigan & Barroso, 2016; Horigan, Schneider, Docherty, & Barroso, 2013; Lee, Lin, Chaboyer, Chiang, & Hung, 2007; Yngman‐Uhlin, Friedrichsen, Gustavsson, Fernström, & Edéll‐Gustafsson, 2010). These studies offer valuable insights into the dominance of biomedical causal attributions for fatigue, the role of sleep quality in further exacerbating fatigue, and pervasiveness of passive fatigue management strategies (Horigan et al ., 2013; Lee et al ., 2007; Yngman‐Uhlin et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Complications such as uremia, anemia, myopathy, and neuropathy decrease muscular strength, cardio-pulmonary fitness, and quality of life, [14,15] which is why this population is seen more frequently in physiotherapy practice currently.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that adults with CKD experience limitations in their daily life due to insufficient physical fitness. In a previous study (Heiwe et al 2003) it was shown that adult with CKD experience fatigue both mental and physical fatigue. This results in a reduced physical fitness and reduced physical functioning in terms of impact on performance and endurance.…”
Section: Hormone Systemmentioning
confidence: 97%
“…Insulin-like growth factor (IGF-1) could also be produced locally in the muscle but the systemic effect is unclear. Kouidi et al 1998;Heiwe et al 2003;Johansen et al 2003;Heiwe et al 2005). It is declining from 70% of the expected norm in a pre-uremic phase to 50% of the expected norm when starting dialysis therapy (Painter et al 1986;Kettner-Melsheimer et al 1987;Brodin et al 2001).…”
Section: Hormone Systemmentioning
confidence: 99%
See 1 more Smart Citation